"ProGRess" - Prokrastination reduzieren und Gesundheit fördern. - Schneider, Tamara; Klingsieck, Katrin B.

"ProGRess" - Prokrastination ressourcenstark und gesundheitsfördernd begegnen. - Schneider, Tamara; Klingsieck, Katrin B.

"ProGRess" - Ressourcen gegen Prokrastination aktivieren und Gesundheit fördern. - Schneider, Tamara; Klingsieck, Katrin B.

Dokumentation der Erhebungsinstrumente des Projekts WiGeMath - Schürmann, Mirko; Büdenbender-Kuklinski, C.; Lankeit, Elisa; Liebendörfer, Michael; Hochmuth, R.; Biehler, Rolf; Schaper, N.

Einblicke in explizite und implizite Erwartungen Lehrender an Studierendentexte. Textbasierte Interviews zu Zielen und Erträgen von fachsensiblem Peer-Textfeedback - Karsten, Andrea (Schreiblehrkonzepte an Hochschulen. Fallstudien und Reflexionen zum fachspezifischen Schreibenlehren und -lernen)

(Selbst-)Kritik und (Selbst-)Reflexion. Fragen stellen, Stimmen identifizieren, Referenzpunkte finden. - Karsten, Andrea (JoSch - Journal der Schreibwissenschaft)

TVA in the wild: Applying the theory of visual attention to game-like and less controlled experiments - Krüger, Alexander; Tünnermann, Jan; Stratmann, Lukas; Briese, Lucas; Dressler, Falko; Scharlau, Ingrid (Open Psychology)
As a formal theory, Bundesen’s theory of visual attention (TVA) enables the estimation of several theoretically meaningful parameters involved in attentional selection and visual encoding. As of yet, TVA has almost exclusively been used in restricted empirical scenarios such as whole and partial report and with strictly controlled stimulus material. We present a series of experiments in which we test whether the advantages of TVA can be exploited in more realistic scenarios with varying degree of stimulus control. This includes brief experimental sessions conducted on different mobile devices, computer games, and a driving simulator. Overall, six experiments demonstrate that the TVA parameters for processing capacity and attentional weight can be measured with sufficient precision in less controlled scenarios and that the results do not deviate strongly from typical laboratory results, although some systematic differences were found.

The time course of salience: not entirely caused by salience - Krüger, Alexander; Scharlau, Ingrid (Psychological Research)
Visual salience is a key component of attentional selection, the process that guards the scarce resources needed for conscious recognition and perception. In previous works, we proposed a measure of visual salience based on a formal theory of visual selection. However, the strength of visual salience depends on the time course as well as local physical contrasts. Evidence from multiple experimental designs in the literature suggests that the strength of salience rises initially and declines after approximately 150 ms. The present article amends the theory-based salience measure beyond local physical contrasts to the time course of salience. It does so through a first experiment which reveals that—contrary to expectations—salience is not reduced during the first 150 ms after onset. Instead, the overall visual processing capacity is severely reduced, which corresponds to a reduced processing speed of all stimuli in the visual field. A second experiment confirms this conclusion by replicating the result. We argue that the slower stimulus processing may have been overlooked previously because the attentional selection mechanism had not yet been modeled in studies on the time course of salience.

Advances in the application of a computational Theory of Visual Attention (TVA): Moving towards more naturalistic stimuli and game-like tasks - Tünnermann, Jan; Kristjansson, Arni; Petersen, Anders; Schubö, Anna; Scharlau, Ingrid (Open Psychology)
The theory of visual attention, “TVA”, is an influential and formal theory of attentional selection. It is widely applied in clinical assessment of attention and fundamental attention research. However, most TVA-based research is based on accuracy data from letter report experiments performed in controlled laboratory environments. While such basic approaches to questions regarding attentional selection are undoubtedly useful, recent technological advances have enabled the use of increasingly sophisticated experimental paradigms involving more realistic scenarios. Notably, these studies have in many cases resulted in different estimates of capacity limits than those found in studies using traditional TVA-based assessment. Here we review recent developments in TVA-based assessment of attention that goes beyond the use of letter report experiments and experiments performed in controlled laboratory environments. We show that TVA can be used with other tasks and new stimuli, that TVA-based parameter estimation can be embedded into complex scenarios, such as games that can be used to investigate particular problems regarding visual attention, and how TVA-based simulations of “visual foraging” can elucidate attentional control in more naturalistic tasks. We also discuss how these developments may inform future advances of TVA.

Kontaktlos lehren? - Reis, Oliver; Jenert, Tobias; Scharlau, Ingrid (Hochschule auf Abstand)

Wer bestimmt die Hochschullehre? - Reinmann, Gabi; Kreber, Carolin; Bremer, Helmut; Langemeyer, Ines; Scharlau, Ingrid (Hochschullehre im Spannungsfeld zwischen individueller und institutioneller Verantwortung: Tagungsband der 15. Jahrestagung der Gesellschaft für Hochschulforschung)

Jean Piaget als - was? - Scharlau, Ingrid (Interdisziplinarität als fachdidaktische Herausforderung: Psychologie im Schulfach Erziehungswissenschaft)

The digital home learning environment and its relation to children’s ICT self-efficacy - Bonanati, Sabrina; Buhl, Heike M. (Learning Environments Research)
With the rapid progress of technological development, self-efficacy in reference to digital devices (i.e., information and computer technology [ICT] self-efficacy) is an important driver that helps students to deal with technological problems and support their lifelong learning processes. Schools, peers, and home learning environments are important sources for the development of positive self-efficacy. Expanding on previous research, we investigated the associations between different aspects of the digital home learning environment and students’ ICT self-efficacy. The moderation effects of gender were also tested. A total of 651 children answered a questionnaire about different digital home learning environment dimensions and estimated their ICT self-efficacy using an adapted scale—Schwarzer and Jerusalem’s (1999) general self-efficacy scale. Using the structural equation modeling technique, a digital home learning environment containing six different qualities of parental support was investigated. Families’ cultural capital, parents’ attitudes toward the Internet, and shared Internet activities at home contributed positively to ICT self-efficacy. We observed small gender differences, with the moderation effect being nonsignificant. The results help researchers and practitioners to understand how different dimensions of the digital home learning environment support ICT self-efficacy. We will discuss how parents can enhance the home learning environment and how teachers can integrate this knowledge into formal education.
Keywords: Digital media use; Gender; Home learning environment; ICT self-efcacy; Motivation; Parental involvement

Latent Congruence Model to Investigate Similarity and Accuracy in Family Members' Perception: The Challenge of Cross-National and Cross-Informant Measurement (Non)Invariance - Tagliabue, Semira; Zambelli, Michela; Sorgente, Angela; Sommer, Sabrina; Hoellger, Christian; Buhl, Heike M.; Lanz, Margherita (Frontiers in Psychology)
Several methods are available to answer questions regarding similarity and accuracy, each of which has specific properties and limitations. This study focuses on the Latent Congruence Model (LCM; Cheung, 2009), because of its capacity to deal with cross-informant measurement invariance issues. Until now, no cross-national applications of LCM are present in the literature, perhaps because of the difficulty to deal with both cross-national and cross-informant measurement issues implied by those models. This study presents a step-by-step procedure to apply LCM to dyadic cross-national research designs controlling for both cross-national and cross-informant measurement invariance. An illustrative example on parent–child support exchanges in Italy and Germany is provided. Findings help to show the different possible scenarios of partial invariance, and a discussion related to how to deal with those scenarios is provided. Future perspectives in the study of parent–child similarity and accuracy in cross-national research will be discussed.
Keywords: latent congruence model; measurement invariance; similarity; accuracy; cross-national; cross-informant; parent-child relationship; support exchanges

Intergenerational Value Similarity and Subjective Well-Being - Hoellger, Christian; Sommer, Sabrina; Buhl, Heike M. (Journal of Family Issues)
This investigation concentrates on the association of intergenerational value similarity and adult children’s and parents’subjective well-being, on the linkage between relationship quality and subjective well-being. Mediation effects of the relationship quality on the associations between value similarity and subjective well-being were focused. The sample consisted of 600 adult German children (53.8% women) and their parents. Dyadic correlations were constructed to determine the value similarity. In this study, the general value orientation and the family values were objects of research. We measured the subjective well-being with the Satisfaction with Life Scale and we used the Network of Relationships Inventory (NRI) to measure the relationship quality. Associations between subjective well-being and value similarity, and between subjective well-being and relationship quality, as well as mediation effects, were found. All effects depend on gender and perspective.
Keywords: adult child–parent dyads; relationship quality; life satisfaction; parent–child relationship; intergenerational stake hypothesis; mediation analyses

Zusammenhang zwischen der familiären Lebenssituation und Werteähnlichkeiten in der Eltern-Kind-Beziehung im Erwachsenenalter - Hoellger, Christian; Sommer, Sabrina; Buhl, Heike M. (Zeitschrift für Soziologie der Erziehung und Sozialisation)
Die Querschnittsuntersuchung beschäftigt sich mit der Fragestellung, ob in Zusammenhang mit der familiären Lebenssituation Erwachsener (Elternstatus und Beziehungsstatus) Unterschiede hinsichtlich der Werteähnlichkeit zwischen ihnen und ihren Eltern bestehen. Dabei wurde die Ähnlichkeit der individuellen Grundwerte nach Schwartz (1992) fokussiert. Die Werteähnlichkeit wurde mittels dyadischer Korrelationen bestimmt (Kenny & Winquist, 2001). Die Stichprobe bestand aus N= 1047 Dyaden. Dafür nahmen 600 erwachsene Kinder (53.8 % weiblich) mit ihren Eltern (542 Mütter und 505 Väter) teil. Das Alter der teilnehmenden Kinder lag zwischen 25 und 49 Jahren (M= 33.9, SD = 6.1). Die Ergebnisse dieser Studie zeigten, dass sich die Werteähnlichkeiten in Abhängigkeit von der familiären Lebenssituation unterschieden: Die Elternschaft der erwachsenen Kinder ging mit einer größeren Werteähnlichkeit in der Mutter-Kind-Dyade einher. Ebenso konnte eine größere Werteähnlichkeit zwischen verheirateten Söhnen und deren beiden Elternteilen beobachtet werden, verglichen mit den Söhnen, die Single oder in einer Partnerschaft waren. Die Werteähnlichkeit der Töchter zu ihren Eltern unterschied sich nicht in Abhängigkeit des Beziehungsstatus.

„Power-Posen“ – Fakten, frisierte Daten, Forschungslyrik? Eine Unterrichtsreihe zu Praktiken und Darstellungsformen psychologischer Forschung - Scharlau, Ingrid; Patrzek, Justine; Schreiber, Christine (Unterrichtsmaterial des Verbandes der Psychologielehrerinnen und –lehrer)
Keywords: Unterrichtsfach Psychologie

Kompetenzdiagnose in der Berufsbildung von Pflegelehrpersonen - Schürmann, Mirko; Bender, Elena; Grebe, Christian (Gruppe. Interaktion. Organisation. Zeitschrift für Angewandte Organisationspsychologie (GIO))
Zusammenfassung In diesem Beitrag der Zeitschrift Gruppe. Interaktion. Organisation. (GIO) wird das Instrument zur Diagnose pädagogischer Kompetenzen von Pflegelehrpersonen (PädKomPflege) vorgestellt. Die Berufsbildung in der Pflege ist durch sich verändernde inhaltliche und gesetzliche Anforderungen geprägt. Verschiedene landesspezifische rechtliche Vorgaben führen zu einem sehr heterogenen Bild von Qualifikationen und Kompetenzen der Pflegelehrpersonen. Die Anrechnung bereits erworbener Kompetenzen auf pflegepädagogische Studiengänge sowie die Kompetenzerfassung und -bilanzierung in Berufsbildungseinrichtungen spielt daher eine wichtige Rolle. Vor diesem Hintergrund wurde das Instrument PädKomPflege entwickelt und erprobt. Grundlage des Kompetenzmodells sind die Empfehlungen der Kultusministerkonferenz (2004) zu den Standards für die (allgemeine) Lehrerbildung sowie Expertenworkshops und -interviews mit PflegedidaktikerInnen. Die empirische Erprobung erfolgte an einer Stichprobe von 1096 Pflegelehrpersonen. Psychometrische Analysen auf Grundlage der klassischen Testtheorie sowie IRT-basierte Analysen führten zu einer Überarbeitung des Instruments, welches nun als zweisprachiges Online-Self-Assessmenttool (eng./deut.) vorliegt. Die Validierung der deutschsprachigen Version fand anhand von 545 TeilnehmerInnen im Jahr 2016 statt, sodass ein geprüftes Instrument mit 54 Items in den fünf Hauptskalen (Unterricht, Beurteilung, Beratung, Lernortkooperation sowie Organisations- und Schulentwicklung) und 18 Subskalen zur Verfügung steht. Sowohl klassische als auch probabilistische Testgütekriterien werden erfüllt. Die Skalen weisen hohe interne Konsistenzen auf ( α > 0,80) und sind überwiegend konstruktvalide. So lassen sich für 17 der 18 Subskalen ordinale Raschmodelle anpassen. Auf der Ebene der Hauptskalen können Partial Credit Modelle für alle Items von modellkonformen Subskalen einer Hauptskala angepasst werden. Das Instrument kann zur individuellen Kompetenzdiagnostik, zur Identifikation von Bildungsbedarfen in Schulen des Gesundheitswesens und im Kontext beruflicher Bildungsprozesse genutzt werden. In der Onlineversion erhalten Teilnehmende abschließend ein individuelles Kompetenzprofil mit möglichen Vergleichswerten. Das Tool kann begleitend zu Qualifizierungsprozessen als Monitoring-Instrument oder zur individuellen Kompetenzbilanzierung eingesetzt werden.
Keywords: Organizational Behavior and Human Resource Management; Applied Psychology; Developmental and Educational Psychology; Education; Social Psychology

Die Health Professionals Competence Scales (HePCoS) zur Kompetenzerfassung in den Gesundheitsfachberufen. Technical Report - Grebe, Christian; Schürmann, Mirko; Latteck, Änne-Dörte

Die Rolle von arbeitsplatzbezogener Flexibilisierung und die Betrachtung von individuellen Werten für Mitarbeitendenbindung in der Arbeitswelt 4.0 - Bender, Elena; Schürmann, Mirko; Poethke, Ute; Soyka, Chantal; Schaper, Niclas; Rowold, und Jens (Zeitschrift für Arbeits- und Organisationspsychologie A&O)
Zusammenfassung. In der Arbeit 4.0 ist durch neue Beschäftigungsmöglichkeiten für Mitarbeitende eine Langzeitbindung an ein Unternehmen seltener. Unternehmen reagieren mit flexibilisierten Arbeitsplätzen, um diesem Wunsch der Mitarbeitenden nachzukommen. Flexibilisierung reduziert die Absicht das Unternehmen zu verlassen. Dabei ist wichtig, räumliche und zeitliche Flexibilisierung zu differenzieren. Außerdem gewinnen individuelle Werte bezüglich Stabilität und Kontinuität an Bedeutung und können den Bindungswunsch stärken. Hauptziel dieser Untersuchung ist, anhand eines kontroll- und ressourcentheoretisch fundierten Rahmens in zwei aufeinander aufbauenden Studien ( N = 448, N = 202) die (potenziell unterschiedlich starken) Zusammenhänge von zeitlicher und räumlicher Flexibilisierung mit Mitarbeitendenbindung zu analysieren und zu prüfen, ob sich diese Zusammenhänge bestätigen lassen, wenn zusätzlich individuelle Werte in die Analyse einbezogen werden. Die Ergebnisse zeigen, dass zeitliche und räumliche Flexibilisierung unterschiedlich mit der Bleibeabsicht zusammenhängen. Während zeitliche Flexibilisierung positive Zusammenhänge zeigt, finden sich in Bezug auf räumliche Flexibilisierung keine Zusammenhänge. Werte bezüglich Stabilität und Kontinuität scheinen dabei nicht mit einer stärkeren Mitarbeitendenbindung zusammenzuhängen.
Keywords: Organizational Behavior and Human Resource Management; Applied Psychology

Work Characteristics or Workers’ Characteristics? An Input-Process-Output Perspective on Informal Workplace Learning of Blue Collar Workers. - Decius, Julian; Schaper, Niclas; Seifert, Andreas (Vocations and Learning)

Bildungswissenschaftliches Wissen und Kompetenzselbsteinschätzungen unter Berücksichtigung individueller Voraussetzungen. Ergebnisse der Befragung angehender Lehrkräfte im Praktikum. - Seifert, Andreas; Caruso, Carina (PraxisForschungLehrer*innenBildung. Zeitschrift für Schul- und Professionsentwicklung.)

„Allgemein hat sich die psychische Gesundheit vieler Schüler verschlechtert…” – Belastungserleben als Herausforderung von Abiturientinnen und Abiturienten im digital vermittelten Distanzunterricht. - Rogge, Tm; Seifert, Andreas (DigiGebf21)

„Ich weiß die Antwort nicht“ – Ein Mangel an Motivation oder ein Mangel an Wissen? - Watson, Christina; Seifert, Andreas (PAEPSY 2021)

Building, emptying out, or dreaming? Action structures and space in students’ metaphors of academic writing - Scharlau, Ingrid; Karsten, A.; Rohlfing, Katharina J. (Journal of Writing Research)
Keywords: Literature and Literary Theory; Linguistics and Language; Language and Linguistics; Education

Prospektive und prozessbezogene Kompetenzanalyse - Gestaltung und Erprobung eines Vorgehens - Depenbusch, Sarah; Bender, Elena; Schaper, Niclas

Investigating the multidimensionality of informal learning: Validation of a short measure for white‐collar workers - Decius, Julian; Knappstein, Michael; Schaper, Niclas; Seifert, Andreas (Human Resource Development Quarterly)
Keywords: Organizational Behavior and Human Resource Management; Arts and Humanities (miscellaneous)

The Hen-Egg-Problem of Informal Workplace Learning & Work Design: The Mediating Role of Job Crafting. - Decius, Julian; Schaper, Niclas; Seifert, Andreas (Academy of Management Prodeedings)

„Power Poses“ – Fakten, frisierte Daten, Forschungslyrik? Ein Unterrichtsvorhaben zu Praktiken und Darstellungsformen psychologischer Forschung am Beispiel von nonverbaler Kommunikation - Schreiber, Christine; Scharlau, Ingrid; Patrzek, Justine (Psychologieunterricht)
Keywords: Unterrichtsfach Psychologie

Unterrichtsfach Psychologie an der Universität Paderborn - Patrzek, Justine; Buhl, Heike M.; Scharlau, Ingrid (Psychologieunterricht)
Keywords: Unterrichtsfach Psychologie

Schule in der digitalen Welt - Buhl, Heike M.; Bonanati, Sabrina; Eickelmann, Birgit

Schreiben als Schlüsselkompetenz? - Scharlau, Ingrid; Haacke, Stefanie; Karsten, Andrea; Lahm, Swantje (Handbuch Hochschuldidaktik)

Big-M-small-N temporal-oder judgment data - Tünnermann, Jan; Scharlau, Ingrid (The Quantitative Methods of Psychology)

Prokrastination bei Studierenden verringern durch Anwendung eines Ratgebers im Gruppensetting - Korsmeier, Teresa; Bobe, Julia; Klingsieck, Katrin B. (Zeitschrift für Beratung und Studium)

Teilhabe von Eltern an schulischem Lernen mit Family-Literacy-Programmen. Langzeiteffekte von „LIFE – Lesen in Familie erleben“ auf die elterliche Unterstützung beim Lesenlernen - Bonanati, Sabrina; Gruchel, Nicole; Kurock, Ricarda; Buhl, Heike M. (Die Deutsche Schule)
Family-Literacy-Programme stellen eine gute Möglichkeit dar, Eltern in Bildungsprozesse einzubeziehen. Am Beispiel des Programms „LIFE – Lesen in Familie erleben“ wird die Wirkung auf elterliche Unterstützung beim Lesenlernen von Erstklässler*innen unter Einbezug von Eltern- und Kinderperspektive untersucht. Sowohl direkt nach dem Programm als auch ein halbes Jahr später wirkte das Programm positiv auf verschiedene Arten der Anschlusskommunikation beim gemeinsamen Lesen.
Keywords: Kooperation; Familie; Lesekompetenz; Längsschnittstudie; Intervention

Explanation as a Social Practice: Toward a Conceptual Framework for the Social Design of AI Systems - Rohlfing, Katharina J.; Cimiano, Philipp; Scharlau, Ingrid; Matzner, Tobias; Buhl, Heike M.; Buschmeier, Hendrik; Esposito, Elena; Grimminger, Angela; Hammer, Barbara; Haeb-Umbach, Reinhold; Horwath, Ilona; Hüllermeier, Eyke; et al. (IEEE Transactions on Cognitive and Developmental Systems)
One objective of current research in explainable intelligent systems is to implement social aspects in order to increase the relevance of explanations. In this paper, we argue that a novel conceptual framework is needed to overcome shortcomings of existing AI systems with little attention to processes of interaction and learning. Drawing from research in interaction and development, we first outline the novel conceptual framework that pushes the design of AI systems toward true interactivity with an emphasis on the role of the partner and social relevance. We propose that AI systems will be able to provide a meaningful and relevant explanation only if the process of explaining is extended to active contribution of both partners that brings about dynamics that is modulated by different levels of analysis. Accordingly, our conceptual framework comprises monitoring and scaffolding as key concepts and claims that the process of explaining is not only modulated by the interaction between explainee and explainer but is embedded into a larger social context in which conventionalized and routinized behaviors are established. We discuss our conceptual framework in relation to the established objectives of transparency and autonomy that are raised for the design of explainable AI systems currently.
Keywords: Explainability; process ofexplaining andunderstanding; explainable artificial systems

Building, emptying out, or dreaming? Action structures and space in undergraduates’ metaphors of academic writing - Scharlau, Ingrid; Karsten, Andrea; Rohlfing, Katharina (Journal of Writing Research)
The aim of the present study is to bring new momentum into research on students’ understanding of academic writing. Drawing on the idea that metaphors give insight into implicit conceptions of abstract entities and processes, we developed a detailed and differentiated set of conceptual metaphors that can be used to study student ideas about writing in research, teaching, and interventions. A large sample of undergraduates produced their everyday understanding of writing in short texts beginning with a self-generated metaphor. Based on theories from cognitive linguistics, the conceptual metaphors in their texts were analyzed in terms of their action quality (transitivity) and spatiality (spatial primitives). The undergraduates’ conceptualizations were very heterogeneous. Most metaphors depart strongly from scientific approaches to academic writing within cognitive psychology and sociocultural theory. Roughly half of the metaphors could be collated to one of four metaphor systems. Depending on the desired degree of abstraction or concreteness, conceptual metaphors or metaphor systems can be employed in further studies to illuminate thinking about writing.
Keywords: metaphor analysis; academic writing; transitivity; spatial primitives

Consultation Phases in Mathematics Learning and Support Centres - Schürmann, Mirko; Panse, Anja; Shaikh, Zain; Biehler, Rolf; Schaper, Niclas; Liebendörfer, Michael; Hilgert, Joachim (International Journal of Research in Undergraduate Mathematics Education)
Abstract Mathematics Learning Support Centres are becoming more and more common in higher education both internationally and in Germany. Whereas it is clear that their quality largely depends on a functioning interaction in consultations, little is known about how such consultations proceed in detail. On the basis of models from the literature and recorded support sessions (N = 36), we constructed a process model that divides consultations into four ideal–typical phases. In the individual consultations, forward or backward leaps occur, but overall the model seems to describe the data well. A high intercoder reliability shows that it can be applied consistently on real data by different researchers. An analysis of the consultations between students and tutors shows that both mainly work on past attempts or thoughts of the students to solve the exercise or problems and on concrete strategies to solve a problem within the session. In contrast, very little time is dedicated to summarizing and reflecting the solution. The data allows for a more in-depth discussion of what constitutes quality in advising processes and how it might be further explored. Practically, the model may structure support sessions and help in focussing on different goals in different phases.
Keywords: Education; Mathematics (miscellaneous)

Opportunities and Possibilities of a Network of Mathematical Learning and Support Centres in Germany - Schürmann, Mirko; Liebendörfer, Michael; Gildehaus, Lara; Schaper, Niclas; Hochmuth, Reinhard; Biehler, Rolf; Lankeit, Elisa; Kuklinski, Christiane; Ruge, Johanna (Sigma newsletter)

Wann bin ich wer? Peer-Berater*innen im Spannungsverhältnis - Lebock, Sarah (Journal der Schreibberatung)
Peer-Berater*innen nehmen während eines Beratungsgespräches teilweise intuitiv, teilweise bewusst verschiedene Rollen ein. Dieser Artikel soll einen Beitrag zur Reflexion über das Spannungsverhältnis zwischen der Experten- und Prozessberatungsrolle leisten, um die Selbstprofessionalisierung in der Rolleneinnahme zu fördern. Dafür werden auf theoretischer Ebene die konträren Arbeitsweisen beleuchtet, auf denen beide Rollen basieren. Zur Betrachtung von möglichen Einflussfaktoren auf die Rolleneinnahme wird ein selbst entwickeltes Modell präsentiert, welches zum Austausch über diese Faktoren motivieren soll. Zuletzt wird eine praktische Möglichkeit zur gezielten Reflexion über die eigene Rolleneinnahme anhand eines Fragebogens vorgeschlagen.
Keywords: Expertenberatung; Prozessberatung; Rolleneinnahme; Selbstprofessionalisierung

Disziplin Schreibwissenschaft? Kritische Überlegungen zur Entwicklung einer „Practical Art“ - Girgensohn, Katrin; Haacke, Stefanie; Karsten, Andrea (Schreibwissenschaft - eine neue Disziplin: Diskursübergreifende Perspektiven)
Formiert sich eine Disziplin „Schreibwissenschaft“? Wir versuchen, die Form, den Gegenstand und mögliche Ziele des Feldes zu beschreiben, aus dem sich aktuell so etwas wie eine Disziplin zu bilden scheint. Nach einer Vergewisserung, was in der Wissenschaftssoziologie überhaupt unter Disziplin verstanden wird, arbeiten wir Spezifika einer Schreibwissenschaft als einer Practical Art heraus und diskutieren dann, welche Türen sich mit der Institutionalisierung einer Disziplin möglicherweise öffnen werden und welche sich vielleicht schließen.

Der Schreibprozess als Dialog. Eine Perspektive am Schnittpunkt von dialogischer Sprachwissenschaft und soziokultureller Psychologie - Karsten, Andrea (Schreibforschung interdisziplinär)

Fachkulturen unter der Lupe: Metaphern in Reflexionen über die Lehre - Scharlau, Ingrid (die hochschullehre)
Metaphern spielen Ansätzen der Kognitiven Linguistik zufolge eine wichtige Rolle dafür, sich abstrakte Sachverhalte zu erschließen. Die Autorin analysiert zwei Interviews über Fachkulturen aus einer früheren Untersuchung (Scharlau und Huber 2019) auf ihre wichtigsten lehrbezogenen Metaphern. Diese werden auf der Basis von kognitiv-linguistischen Ansätzen und Methoden interpretiert und Ansätze für eine hochschuldidaktische Nutzung eines solchen Blickwinkels skizziert.
Keywords: Fachkultur; Fachkulturen; Metapher

Digitalisierung in der Lehrerbildung durch Communities of Practice. Konzeption, Governance und Qualitätsmanagement des ComeIn-Verbundvorhabens in Nordrhein-Westfalen - van Ackeren, Isabell; Buhl, Heike M.; Eickelmann, Birgit; Heinrich, Martin; Wolfswinkler, Günther (Bildung, Schule und Digitalisierung)

Intergenerational Value Similarity in Adulthood - Hoellger, Christian; Sommer, Sabrina; Albert, Isabelle; Buhl, Heike M. (Journal of Family Issues)
This investigation concentrates on value similarity between parents and their children during adulthood. The interplay between gender, age, relationship quality, and frequency of contact on value similarity was analyzed. A total of 600 adult German children (53.8% women) and their parents took part in a questionnaire study. Value orientation was measured with a short version of Schwartz’s Portrait Values Questionnaire, and relationship quality with the Network of Relationships Inventory (Furman & Buhrmeister, 1992).Value similarity was higher in mother–daughter dyads compared to mother–son dyads, but in the other dyads, no significant differences were found. Regarding relationship quality, verbal intimacy was not related to value similarity. Parental satisfaction was associated with value similarity in the father–child dyads. Satisfaction, as perceived by adult children, was linked to value similarity in mother–child and father–son dyads. Furthermore, the frequency of contact related to value similarity between mothers and sons.
Keywords: Adult child–parent dyads; value similarity; relationship quality; frequency of contact; parent-child-relationship

Analytical Competence of Teachers – Assessing the Construct Validity by Means of Mixed Methods and Drawing Consequences for Teacher Education. - Plöger, Wilfried; Krepf, Matthias; Scholl, Daniel; Seifert, Andreas (Teacher Education Quaterly)

Lesekompetenz fördern. Ein Manual für das LIFE-Programm zur Stärkung der Zusammenarbeit von Schule und Elternhaus - Bonanati, Sabrina; Greiner, Christian; Gruchel, Nicole; Buhl, Heike M.

Assessment of the quality of end-of-life care: translation and validation of the German version of the “Care of the Dying Evaluation” (CODE-GER) – a questionnaire for bereaved relatives. - Vogt, Annika; Stiel, Stephanie; Heckel, Maria; Goebel, Swantje; Mai, Sandra Stephanie; Seifert, Andreas; Gerlach, Christina; Ostgathe, Christoph; Weber, Martin (Health and Quality of Life Outcomes)

Investigating the Hen-Egg-Problem: A Cross-Lagged-Panel Approach to Informal Workplace Learning and Working Conditions. - Decius, Julian; Schaper, Niclas; Seifert, Andreas (9th PDRnet Research Symposium)

In Zeiten von p-hacking und fake science: Wissenschaftsorientierung als Herausforderung an die Psychologiedidaktik - Scharlau, Ingrid; Schreiber, Christine (Psychologie unterrichten in Deutschland, Österreich und der Schweiz: Leitlinien und Grundlagen)
Keywords: Unterrichtsfach Psychologie